CONVERGENCE AND CONFLICT: THE “STRUCTURE” AND POLICIES AFFECTING RELATIONS BETWEEN RUSSIA, CHINA, AND THE UNITED STATES - ROZMARIN, Leon (CENTRAL ASIA AND THE CAUCASUS, 2011)
Central Asia, much like other regions of Eurasia, has witnessed tensions and cooperation between the United States, Russia, and China. It is also recognized that Central Asia has its own regional dynamics that intertwine with the global inter-state relations, giving strong international tinge to local events and drawing-in extra regional competition and tensions. Within the above theme is another—the hegemonic rise of China and the expected, or even existent, balancing response by Russia.1 However, Central Asia has so far witnessed more Russo-Chinese cooperation than competition while experiencing more Russo-American competition than cooperation, a trend likely to continue in the medium term. Suspicions and tensions in Russo-American relations are matched by similar trends in Sino-American strategic interaction. Russian national doctrines, and its policymakers, have repeatedly emphasized the extremist-terrorist threats and the U.S.-NATO preponderance and policies, including the ABM initiative and militarization of space, as the main nonstate threats and state-based challenges, respectively. In this environment, China is an important regional and strategic partner, part of the response to challenges. Over the past twenty years and for the medium term, the major structural factors in relations between the three powers are the diverging priority vectors of Russian and Chinese foreign and security policies—toward the west and east, respectively—combined with the global power of the United States which confronts these states in Europe-CIS and East Asia, providing a measure of common interests to Russo-Chinese relations. On a number of important strategic issues, these interests converge on the U.S. problem—joint opposition to American global ABM initiatives, regime change and democratization policies, NATO expansion, competition over Ukraine, the balance of power in Europe and in East Asia. Meanwhile, Central Asia has had to experience elements of this broader competition, but at the same time has provided, and will continue to provide, its own contribution as a force for cooperation and competition, not only as a symptom but as a cause in its own right.